RELATIONSHIP BETWEEN PREVENTIVE BEHAVIOUR AND THE NUMBER OF COVID-19 CASES IN DKI JAKARTA (CASE STUDY OF KEYWORD SEARCH USING GOOGLE TRENDS) - Mochamad Wisnu Samudra; Lilik Zuhriyah; Alidha Nur Rakhmani (Universitas Brawijaya, 2023)
Background: The COVID-19 pandemic has infected a large number of countries in the world, especially Indonesia. One of the most affected provinces in Indonesia is DKI Jakarta. The Indonesian government responded to the COVID-19 pandemic by issuing various policies related to preventive behavior to reduce the addition of COVID-19 cases. Purpose: This study aims to find out how the search for keywords related to COVID-19 prevention behavior via Google Trends relates to the number of COVID-19 cases in DKI Jakarta. Method: Using an analytic observational design with a cross-sectional approach that utilizes Google Trends as a data collection tool. Data related to searches for the prevention of COVID-19 and the number of cases of COVID-19 in DKI Jakarta were collected from 15 March 2020 to 3 January 2021. The data obtained were then analyzed using the Spearman correlation test. Results and Discussion: The results obtained from this study are that there is a significant inverse relationship between the three variables